A Collision Avoidance Strategy for Redundant Manipulators in Dynamically Variable Environments: On-Line Perturbations of Off-Line Generated Trajectories - Cecilia Scoccia; Giacomo Palmieri; Matteo Claudio Palpacelli; Massimo Callegari (Machines, 2021)
In this work, a comprehensive control strategy for obstacle avoidance in redundant manipulation is presented, consisting of a combination of off-line path planning algorithms with on-line motion control. Path planning allows the avoidance of fixed obstacles detected before the start of the robot’s motion; it is based on the potential fields method combined with a smoothing process realized by means of interpolation with Bezier curves. The on-line motion control is designed to compensate for the motion of the obstacles and to avoid collisions along the kinematic chain of the manipulator; it is realized by means of a velocity control law based on the null space method for redundancy control. A new term is introduced in the control law to take into account the speed of the obstacles as well as their position. Simulations on a simplified planar case are presented to assess the validity of the algorithms and to estimate the computational effort in order to verify the transferability of our approach to a real system.